Substance Abuse Among Medical Students in Baghdad: An Updated Concise Descriptive Study - Younis, Maha S.; Jassim, Ashraf A.; Ibrahim, Huda W.; Khuraisan, Asala A. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Substance abuse can be defined briefly as the excessive and continuous consumption of psychoactive substances without medical supervision, leading to dependence and adverse health consequences. Substance abuse is an escalating and surging public health challenge in Iraq. Objectives: To assess the frequency of substance abuse among a large group of senior undergraduate medical students and to identify the associated factors. Methods: A convenience sample of 388 senior medical students from the College of Medicine/ University of Baghdad during April 2023 took part in this study. Itemployed a modified electronic version of the Drug Addiction Survey Questionnaire (DAST-20) with “yes or no” responses through the college’s website anonymously. The survey format included questions about the type, quantity, and duration of abuse, the respondent’s gender and the causes of abuse. Three more questions about the use of alcohol, caffeine, and nicotine were added to the 20 original questions. This study was affiliated with the Department of Community Medicine Results: Out of the 388 respondents, 212 students (54.6%) met the criteria for substance abuse according to the study tool. The substances reported to be used included caffeine beverages 94 (24.2%), tobacco (nicotine) 48 (12.3%), Benzodiazepines 23 (5.9%), over-the-counter (OTC) medicines 21 (5.4%), and steroids 8 (2%). Males reported greater rates of substance abuse for nicotine and illicit substances compared to females. Females had higher substance use rates for caffeine at the Baghdad College of Medicine. Conclusion: The incidence of drug abuse among medical students in Baghdad is rather high, given their level of education and adherence to religious and cultural norms. Coffee, tobacco, and OTC were the most consumed substances, while steroids and sedatives were the least. The use of illegal drugs is higher than before. Tension, anxiety, and depression seem to be the justification